Modular synthesis of functional libraries by accelerated SuFEx click chemistry - Homer, Joshua A; Koelln, Rebecca A; Barrow, Andrew S; Gialelis, Timothy L; Boiarska, Zlata; Steinohrt, Nikita S; Lee, Erinna F; Yang, Wen-Hsuan; Johnson, Robert M; Chung, Taemoon; Habowski, Amber N; Vishwakarma, Dharmendra S; et al. (Chemical science (Cambridge), 2024)
Accelerated SuFEx Click Chemistry (ASCC) is a powerful method for coupling aryl and alkyl alcohols with SuFEx-compatible functional groups. With its hallmark favorable kinetics and exceptional product yields, ASCC streamlines the synthetic workflow, simplifies the purification process, and is ideally suited for discovering functional molecules. We showcase the versatility and practicality of the ASCC reaction as a tool for the late-stage derivatization of bioactive molecules and in the array synthesis of sulfonate-linked, high-potency, microtubule targeting agents (MTAs) that exhibit nanomolar anticancer activity against multidrug-resistant cancer cell lines. These findings underscore ASCC's promise as a robust platform for drug discovery. The Accelerated SuFEx Click Chemistry (ASCC) protocol, adapted to a 96-well plate format, has been applied to the late-stage derivatization of bioactive molecules and array synthesis of anticancer agents, showcasing its potential for drug discovery.